The Comparison of Prosthesis Position in Total Hip Arthroplasty by Lateral and Posterior Incision in Patum Thani Hospital - Kaewkun, Chatchawal (Journal of Health Science of Thailand, 2018)
Prosthetic malalignment is one of the major factor of complications in total hip arthroplasty. There is a long standing belief that to use difference incision can achieve difference alignment. This retrospective analytical study tried to find the difference of prosthetic alignment in total hip arthroplasty with a lateral or posterior incision. The X-ray and medical record of every patient under-going total hip arthroplasty in Pathum Thani hopital from 2002 to 2007 were reviewed. There were 57 patients with 68 hips. The sex, age, and diagnosis showed no statistically significant differences between the two groups. Likewise the acetabular inclination ,vertical height, horizontal distance and anteversion also showed no significant differences between the two groups. Yet the femoral stem alignment tended to be varus in posterior incision and valgus in lateral incision with statistically significance, resulting in the posterior incision group longer offset with statistical significance. It might be the influence of the position of femur while inserting femoral stem. No significant differences of limb length discrepancy between the two groups were reported . This data can be used to prevent prosthetic malalignment in the selected incision in total hip arthoplasty.